Phytochemical Evaluation of Some Medicinal Plants of Puthan District of Nepal - Giri, Hari; Rajbhandari, Meena (Nepal Journal of Science and Technology, 2020)
Different parts of eleven medicinal plants used in the traditional medicine in Puthan district were collected. Three different extracts, methanol, 50% aqueous methanol and 70% aqueous acetone extracts were prepared for each plant material. The methanol extracts were screened for the presence of different classes of phytochemicals. Total phenolic and flavonoid content, as well as DPPH free radical scavenging activity, were evaluated. All the investigated extracts contain a high amount of phenolics and flavonoids.The highest amount of phenolics and flavonoids were detected in the methanol extract of bark of Bauhinia variegate (355.35+3.69 mg GAE/g and 209.23 ±1.25 mg QE/g extract). Among the eight tested extracts, the highest radical scavenging activity was shown by methanol extract of bark of B. variegate (IC50 3.68 μg/ml). The extract having the highest phenolic and flavonoid content showed the lowest IC50 demonstrating the positive correlation between radical scavenging activity and total phenolic and flavonoid content.